Praktik Jual Beli Pada Marketplace Shopee Dan Perlindungan Hukum Bagi Konsumen - fatarib, husnul; Hayati, Suci (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2020)
The practice of buying and selling in the modern era has developed so rapidly. Buying and selling which has long been done face to face. Customers simply search for the desired item on the available marketplace application, then make transactions for the desired item. As is well known, the market place is a market for all kinds of goods that can be traded. Among the many marketplace applications, one of which is Shopee in this application also provides direct buying and selling and cash payments by transfer, then there is also a sale and purchase where the payment is made when the goods are received by the buyer / paid on the spot (COD), even buying and selling is available. which is done on credit. Of the many existing transactions, transaction failures are not uncommon. This means that sometimes there are items that are not in accordance with what the buyer wants. So it becomes necessary for Shopee marketplace application developers to pay more attention to legal protection for consumers who use the Shopee application.